Inhibition of monoamine oxidase activity by antidepressants and mood stabilizers - Fisar, Zdenek; Hroudová, Jana; Raboch, Jirí (Neuro endocrinology letters, 2010)
OBJECTIVE: Monoamine oxidase (MAO), the enzyme responsible for metabolism of monoamine neurotransmitters, has an important role in the brain development and function, and MAO inhibitors have a range of potential therapeutic uses. We investigated systematically in vitro effects of pharmacologically different antidepressants and mood stabilizers on MAO activity. METHODS: Effects of drugs on the activity of MAO were measured in crude mitochondrial fraction isolated from cortex of pig brain, when radiolabeled serotonin (for MAO-A) or phenylethylamine (for MAO-B) was used as substrate. The several antidepressants and mood stabilizers were compared with effects of well known MAO inhibitors such as moclobemide, iproniazid, pargyline, and clorgyline. RESULTS: In general, the effect of tested drugs was found to be inhibitory. The half maximal inhibitory concentration, parameters of enzyme kinetic, and mechanism of inhibition were determined. MAO-A was inhibited by the following drugs: pargyline > clorgyline > iproniazid > fluoxetine > desipramine > amitriptyline > imipramine > citalopram > venlafaxine > reboxetine > olanzapine > mirtazapine > tianeptine > moclobemide, cocaine >> lithium, valproate. MAO-B was inhibited by the following drugs: pargyline > clorgyline > iproniazid > fluoxetine > venlafaxine > amitriptyline > olanzapine > citalopram > desipramine > reboxetine > imipramine > tianeptine > mirtazapine, cocaine >> moclobemide, lithium, valproate. The mechanism of inhibition of MAOs by several antidepressants was found various. CONCLUSIONS: It was concluded that MAO activity is acutely affected by pharmacologically different antidepressants at relatively high drug concentrations; this effect is inhibitory. There are differences both in inhibitory potency and in mechanism of inhibition between both several drugs and the two MAO isoforms. While MAO inhibition is not primary biochemical effect related to their therapeutic action, it can be supposed that decrease of MAO activity may be concerned in some effects of these drugs on serotonergic, noradrenergic, and dopaminergic neurotransmission.
Keywords: Pargyline; thiazepiny; Morpholines; Cocaine; fluoxetin; reboxetin; Affect; Animals; afekt; mirtazapin; Moclobemide; Monoamine Oxidase; Valproic Acid; Antimanic Agents; kyselina valproová; Cyclohexanols; Mianserin; Antidepressive Agents; Citalopram; Iproniazid; Lithium; mitochondrie; pargylin; Mirtazapine; lithium; venlafaxin hydrochlorid; olanzapin; monoaminoxidasa; moklobemid; Mitochondria; mianserin; amitriptylin; Monoamine Oxidase Inhibitors; Swine; Thiazepines; Benzodiazepines; kokain; inhibitory MAO; techniky in vitro; citalopram; morfoliny; zvířata; prasata; Amitriptyline; Cerebral Cortex; Olanzapine; antidepresiva; Reboxetine; Clorgyline; Imipramine; Fluoxetine; klorgylin; benzodiazepiny; desipramin; iproniazid; Desipramine; In Vitro Techniques; cyklohexanoly; Venlafaxine Hydrochloride; imipramin; mozková kůra; antimanika